Experimental Investigation on Flowability and Compaction Behavior of Spray Granulated Submicron Alumina Granules. (6th August 2013) - Choudhary, Abhisek; Ramavath, Pandu; Biswas, Papiya; Ravi, Nukala; Johnson, Roy
Abstract : Aqueous slurry with various solid loadings (up to 40 wt%) of alumina powder (D50 = 300 nm) with suitable rheological properties were spray dried into granules. Solid loading and feed rate of the slurry are found to have a prominent effect on the shape and size distribution of granules. Powder flow measurements exhibited a cohesive index of 28.45 signifying an extremely cohesive flow due to high surface area and irregular morphology. Finer sizes though it offers high geometrical surface area it leads to more surface contacts and hence, high interparticle friction. Spherical morphology achieved through optimum spray drying parameters significantly reduced the cohesive index to 6.45 indicating free flow behavior. Compaction studies of the spray-dried granules and corresponding plot of relative density versus compaction pressure revealed an agglomerate strength of 500 MPa followed by a plateau-like behavior reaching a maximum in the relative density of 59%-60% of the theoretical values.